Prolactin - Nagy, György M.; Toth, Bela E. (IntechOpen, 2013)
Prolactin is a polypeptide hormone that is synthesized in and secreted from the lactotrophs of the anterior pituitary gland. We are now aware that synthesis and secretion of prolactin is not restricted to the anterior lobe of the pituitary gland, but other organs and individual cells can also produce it. This book provides the headlines to follow a course of cumulated knowledge on prolactin research during the last two-three decades and it may also help us understand some of the concerns that we face today.